PERSEPSI SUAMI DALAM PEMILIHAN ALAT KONTRASEPSI DI PUSKESMAS KURANJI PADANG TAHUN 2013 - Oktarina, Risa; Erita, Yeni; Iswandi, Iswandi (STKIP PGRI Sumbar, 2013)
Family planning or family planning program is a program intended to help couples and individuals to achieve their reproductive goals , prevent unwanted pregnancies and reduce the incidence of high-risk pregnancies , but contraceptive use still achieving the lowest compared to other health centers in the city of Padang , where population in the working area Kuranji Health Center in 2009 were 23 595 people spread in 6 village consisting of 14 247 men and women 9,348 people by the number of Eligible Couples (EFA) as many as 3,258 people , so it still takes an effort to increase the knowledge of the acceptor . This study aims to Mendeksripsikan knowledge , attitudes , and participation husband about the use of contraceptives in the Padang region Kuranji Occupational Health Center in 2013.This research is a qualitative research approach is fenomenologys phenomenological approach is rooted in philosophy and psychology , and focuses on the human experience (sociology), the study site clinic Kuranji Padang. Informants of this study is the husband who use contraceptives and health personnel.Data collection techniques using observation, interview and documentation. Analysis using theory Huberman.The results illustrate that the perception of the husband in the use of tools in the District Kuranji Padang kotrasepsi envisaged that the husbands knowledge in the use of contraceptives , especially MOP / vasectomy or condoms are generally pretty good knowledge of the respondent , husbands attitude in the use of contraceptives is quite good , with a positive attitude among husband and wife so many husbands are involved in the use of contraceptives , before use of contraceptives among married terlabih first discuss which one is easier and provide comfort to their husbands in using condoms and contraceptives MOP , sometimes husbands who are proactive in the use of tools kontrasepsi.Partisipasi husband in the use of contraceptives is quite good , because the husband can replace their wives if there are no matches in the use of contraceptives .